"Mucin secreting" and "mucinous" primary thyroid carcinomas: pitfalls in mucin histochemistry applied to thyroid tumours. Issue 8 (August 1987) - Rigaud, C; Bogomoletz, W V
Abstract : Forty primary carcinomas of the thyroid of different histological types were reviewed and studied histochemically, with the aim of identifying and assessing "mucin secretion". The patterns of extracellular "pure alcianophilia" and "mixed alcianophilia" were noted in 7.5% and about 50% of these tumours, respectively. A critical review of the pitfalls in methods and interpretation of mucin histochemistry--as performed in previously reported cases of "mucin secreting" or "mucinous" primary thyroid tumours--is presented. The apparent "mucin secretion" described in these unusual neoplasms could be due to histochemical staining of carbohydrate components or breakdown products of thyroglobulin and colloid.